Mechanisms of γδ T cell accumulation in visceral adipose tissue with aging - Mukherjee, Sujata; Bruno, Maria E. C.; Oakes, Jason; Hawk, Gregory S.; Stromberg, Arnold J.; Cohen, Donald A.; Starr, Marlene E. (Frontiers in Aging, 2024)
γδ T cells are resident in visceral adipose tissue (VAT) where they show an age-associated increase in numbers and contribute to local and systemic chronic inflammation. However, regulation of this population and mechanisms for the age-dependent accumulation are not known. In this study, we identified a progressive trend of γδ T cell accumulation in VAT over the lifespan in mice and explored physiological mechanisms contributing to accumulation. Using isochronic parabiotic pairs of wild-type (WT) and T cell receptor delta knockout (TCRδ KO) mice at young and old age, we confirmed that VAT γδ T cells are predominately a tissue-resident population which is sustained in aging. Migration of peripheral γδ T cells into VAT was observed at less than 10%, with a decreasing trend by aging, suggesting a minor contribution of recruitment to γδ T cell accumulation with aging. Since tissue-resident T cell numbers are tightly regulated by a balance between proliferation and programmed cell death, we further explored these processes. Using in vivo EdU incorporation and the proliferation marker Ki67, we found that the absolute number of proliferating γδ T cells in VAT is significantly higher in the aged compared to young and middle-aged mice, despite a decline in the proportion of proliferating to non-proliferating cells by age. Analysis of apoptosis via caspase 3/7 activation revealed that VAT γδ T cells show reduced apoptosis starting at middle age and continuing into old age. Further, induction of apoptosis using pharmacological inhibitors of Bcl2 family proteins revealed that VAT γδ T cells at middle age are uniquely protected from apoptosis via a mechanism independent of traditional anti-apoptotic Bcl2-family proteins. Collectively, these data indicate that protection from apoptosis at middle age increases survival of tissue-resident γδ T cells resulting in an increased number of proliferative cells from middle age onward, and leading to the age-associated accumulation of γδ T cells in VAT. These findings are important to better understand how adipose tissue dysfunction and related changes in the immune profile contribute to inflammaging among the elderly.